Study on physical and structural properties of yttrium doped barium borate glass / Muhammad Nurfikhri Akmal Dahlan - Dahlan, Muhammad Nurfikhri Akmal (Faculty Of Applied Sciences, 2018)
Six different glass samples have been prepared in this project by melt-quenching technique with composition (75-x) H3BO3·25BaC03-xY203 (where x=O.O, 0.2, 0.4, 0.6,0.8 arid 1.0 mol%). By varying the proportion of H3B03 and BaC03, the effect of Y203 to the barium borate glass, can be investigated in term of physical properties such as density, molar volume and oxygen packing density. The structural properties were measured by X-Ray Diffraction' (XRD) technique and Fourier Transform Infrared (FTIR) spectroscopy. Based on the result, it shows that the density and oxygen packing density increases while the molar volume decreases as the percent of Y203 increases. The amorphous nature of this glass was proved from the XRD spectra. On the FTIR spectra result showed the present of B-O-B bending vibrations, Y-0 molecule which originates from· Y203, bending vibrations of various borate arrangement B-O-B, asymmetric vibrations of B04, B-O stretching vibrations of tetrahedral [B04], modes of boron-oxygen triangular unit and B-O stretching vibrations of [B03].